Cost and Time Control Analysis in the Neucentrix Building Renovation Project Using the Earned Value Method - Pinuji, Putri; Suwandi, Putri Anggi Permata; Rizani, Mohammad Debby (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2025)
In the Neucentrix renovation project, an addendum caused an extension. This study analyzes the weekly performance of the 2023 Neucentrix Pugeran Yogyakarta Project in terms of cost and time using the Earned Value method. The data analyzed using the Earned Value method using ACWP, BCWS, and BCWP indicators. From these indicators, CV, SV, CPI, SPI, EAS and EAC values are obtained. The analysis reveals cost savings from the first to the seventeenth week, with initial acceleration in the first four weeks followed by delays from weeks five to seventeen. The project is expected to take 19 weeks to complete, with a final estimated cost of IDR 2,294,673,540.